Current Pattern of Correlates of Successful Quitting Methods of Tobacco Smoking in Bangladesh - Mahim, Sheikh Sumaya; Uddin, Md Mahfuz; Fahim, Md; Sultana, Papia (International Journal of Statistical Sciences, 2025)
Tobacco smoking remains a significant public health issue, particularly in low- and middle-income countries like Bangladesh, where cessation rates are low despite extensive tobacco control initiatives. The aims of this study are to examine the patterns and prevalence of successful quitting methods for tobacco smoking and to identify the factors associated with successful cessation in Bangladesh. This study is based on a nationally representative sample of 12,783 individuals aged 15 years or older from the Global Adult Tobacco Survey (GATS), 2017. Binary logistic regression has been employed to evaluate significant factors of quitting methods along with descriptive analysis. Counseling by healthcare providers and switching to smokeless tobacco are identified as the most effective cessation strategies. Key correlates of successful quitting include gender, division, occupation, educational level, and wealth index. The model demonstrated good predictive accuracy (Predicted Accuracy = 77.3 and AUC = 0.702). This study highlights the need for targeted, evidence-based interventions to address socio-demographic disparities and promote effective quitting strategies. Future research should focus on longitudinal analyses and exploring alternative cessation methods tailored to susceptible populations in Bangladesh. IJSS, Vol. 25(1), March, 2025, pp 87-98